Hubungan Dukungan Keluarga Dengan Kepatuhan Minum Obat Pada Pasien Skizofrenia Di Poliklinik Rawat Jalan Rumah Sakit Jiwa Kalawa Atei - Saratoga, Rany; Carolina, Putria; Rosela, Kristin (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2025)
Family support plays a key role in helping schizophrenic patients adhere to medication adherence to their relapse prevention. Medication compliance is an important point that patients, families and health workers must be aware of. Mental health is a condition in which an individual can develop physically, mentally, spiritually and socially. Mental disorders will make it difficult for individuals to develop properly. Schizophrenia is a mental disorder that causes an individual’s thoughts, perceptions, emotions and behavior to become distorted. Treatment in schizophrenia takes a long time and adherence to treatment. Research Objective to determine the relationship between family support and medication adherence in schizophrenic patients at Kalawa Atei Psychiatric Hospital. This study used non-experimental quantitative research of unpaired category correlation analysis with a cross sectional approach that emphasizes the time of measurement or observation of independent and dependent variable data only once at a time, then assessed simultaneously and no follow-up. Results: Based on the results of the Chi-Square test, a p value of 0.000 or a significance level of p < 0.05, thus there was a significant relationship between family support and medication adherence in schizophrenia patients at the Kalawa Atei Psychiatric Hospital Polyclinic. Based on the results of the identification of family support for schizophrenic patients at the Kalawa Atei Mental Hospital Polyclinic in Palangka Raya, most of the respondents had good support, namely 17 respondents (56.7%).